Perspektif Generasi Millenial Terhadap Eksistensi Bahasa Indonesia Di Media Sosial - Resviya Resviya (FKIP Universitas Palangka Raya, 2023)
Language is a requirement for humans to think, which is the source of human origins in the process of understanding and knowledge. Regarding the existence of the Indonesian language, the researcher here collects data, records the results of the interviews and analyzes each response from the respondents. This study aims to determine understanding as someone perceives the position of the Indonesian language. The reason for the researcher to make this title is because currently the function of the Indonesian language is felt to be displaced by foreign languages and due to the attitude that believes that it will look modern if you use a foreign language when interacting on social media. This research is useful for readers because when viewed from the problems that have been described, the method needed is to describe the importance of using Indonesian properly and correctly. The research method used is a qualitative research method which is referred to as an investigative approach because researchers usually collect data by face to face with people at the research site. The result of this research is that the Indonesian language has not functioned properly and correctly. Most people who speak feel possessed by a sense of inferiority, so they feel more respected, and educated if in the events of daily narrative, both in the variety of narrative and in writing, they insert a pile of foreign terms, even though there are already equivalent words in Indonesian.